Pengaruh kompetensi, independensi, pengalaman kerja, dan skeptisisme profesional terhadap kualitas audit dengan etika auditor sebagai pemoderasi (studi empiris pada kantor perwakilan badan pengawasan keuangan dan pembangunan Provinsi Riau) - Hutami Dwi Kusuma; Alfiati Silfi; Fajar Odiatma (SYNERGY: Jurnal Bisnis dan Manajemen, 2022)
This study aims to examine the effect of competence, independence, work experience, and professional skepticism on audit quality with auditor ethics as moderating at the Representative Office of the Financial and Development Supervisory Agency of Riau Province. This research is a quantitative research that uses primary data with a questionnaire instrument. The population in this study were all internal auditors who worked at the Representative Office of the Financial and Development Supervisory Agency of Riau Province. The research sample was selected using the non-probability sampling method , the research sample obtained was as many as 53 respondents.software (Statistical Package for Social Science) version 25. The results showed that the independent variables, namely competence, independence, work experience, and professional skepticism had an effect on the dependent variable, namely audit quality. And the moderating variable, namely auditor ethics, is known to not moderate the effect of competence, independence, work experience, and professional skepticism on audit quality